PENGARUH PERCEIVED ORGANIZATION SUPPORT, JOB DEMAND. DAN WORK ENGAGEMENT TERHADAP TURNOVER INTENTION - Luthfian, Ishak; Yulianti, Praptini (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the effect of Perceived Organizational Support, Job Demand, and Work Engagement on Turnover Intention. The study uses a quantitative approach with a survey method on respondents who are employees in the research object. The data were analyzed using regression analysis to test the partial effect of each independent variable on Turnover Intention. The results show that Perceived Organizational Support has a significant positive effect on Turnover Intention. This finding indicates that an increase in the perception of organizational support is followed by an increase in employees' intention to leave the organization, which is not in line with the initial hypothesis and most of the findings of previous studies. Meanwhile, Job Demand and Work Engagement do not show a significant effect on Turnover Intention. These findings imply that the organizational support provided is not yet fully capable of reducing employees' intention to leave and has the potential to be perceived differently by employees, for example, as a form of covert pressure or unmet expectations. Therefore, organizations need to reevaluate the form and implementation of the support provided to be more effective in reducing Turnover Intention